2020
DOI: 10.1002/ange.202003219
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Oriented Clicking (DOC): Divergent Synthesis of SuFExable Pharmacophores from 2‐Substituted‐Alkynyl‐1‐Sulfonyl Fluoride (SASF) Hubs

Abstract: Diversity Oriented Clicking (DOC) is a unified click‐approach for the modular synthesis of lead‐like structures through application of the wide family of click transformations. DOC evolved from the concept of achieving “diversity with ease”, by combining classic C−C π‐bond click chemistry with recent developments in connective SuFEx‐technologies. We showcase 2‐Substituted‐Alkynyl‐1‐Sulfonyl Fluorides (SASFs) as a new class of connective hub in concert with a diverse selection of click‐cycloaddition processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…In this view, alkynyl sulfonyl fluorides 38 provided particularly diverse patterns of heterocycles bearing the SO 2 F moiety (Scheme 18). [166,288]…”
Section: Synthesis Of (Hetero)aromatic Sulfonyl Fluoridesmentioning
confidence: 99%
“…In this view, alkynyl sulfonyl fluorides 38 provided particularly diverse patterns of heterocycles bearing the SO 2 F moiety (Scheme 18). [166,288]…”
Section: Synthesis Of (Hetero)aromatic Sulfonyl Fluoridesmentioning
confidence: 99%
“…Sulfur fluoride exchange (SuFEx) (10), a new generation of click chemistry, has found diverse applications to chemical synthesis (11)(12)(13)(14)(15)(16), materials science (17)(18)(19)(20)(21)(22), chemical biology (23)(24)(25)(26)(27)(28), and drug discovery (29,30). In our previous studies, we demonstrated that SuFEx modification is a highly reliable approach for the late-stage functionalization of drugs and drug-like molecules to generate new compounds with improved properties (31,32).…”
mentioning
confidence: 99%
“…Sulfonyl fluoride reagents have been espoused by Sharpless as click reagents for the reaction with nucleophiles to form sulfonates and sulfonamides, in a process referred to as a SuFEx (sulfur-fluoride exchange) reaction. 5,6,7,28 As first demonstrated in seminal works by Steinkopf 29,30 and others, 31,32,33 the stronger and highly polarised S-F bond confers vastly increased stability to sulfonyl fluorides in comparison to sulfonyl chlorides. The fluoride ion is a poor leaving group and consequently sulfonyl fluorides are highly stable towards nucleophilic substitution as well as reductive and aqueous conditions.…”
Section: Resultsmentioning
confidence: 94%